The rise of the federal colossus : the growth of federal power from Lincoln to F.D.R. - Zavodnyik, Peter, 1969- (Praeger series on American political culture., 2011)
Federal officials contemplated providing jobs to the unemployed as early as the 1870s, while the origins of federal regulation of interstate railroads go back to the Civil War. How and when did the federal government expand the scope of the powers granted to it by the Constitution and evolve into an entity that plays such an enormous role in the lives of ordinary Americans?